HUBUNGAN KEKERASAN VERBAL ORANG TUA DENGAN DISFUNGSI KELUARGA DI KECAMATAN KANDIS KABUPATEN SIAK - Vera Nita Simangunsong; Ria Novianti; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on temporary observations related to verbal abuse with family dysfunctions in Kandis Sub-District, Siak Regency was found, such as: Some parents in Kandis demeaning children and saying harshly, some parents labeling their children, some parents often compare their children to others, some Mother in Kandis works as the head of the household,, some mothers act as responsible for economic needs, and some mothers in Kandis play social responsibility. And based on linearity test it can be seen that the significance value in linearity is 0.003. Because the significance is less than 0.05, it can be concluded that the variables of the parents verbal violence with family dysfunction have a close relationship. From the results of a simple correlation analysis (r) is 0.352 with a probability value of 0.000. Therefore the probability <0.05 (0.000 <0.05) then Ho is rejected this indicates that there is a strong relationship of verbal abuse of parents with family dysfunction. While the direction of the relationship is positive, meaning that the higher the verbal violence of parents, the higher the family dysfunction. The resulting coefficient of determination is equal to r2 = 0.352 with p = 0.003 (p <0.05) so it can be seen that the verbal violence of parents gives a 35.2% influence on family dysfunction.Keywords: Verbal violence, family dysfunction